PELATIHAN PENYUSUNAN LKS BERBASIS AKM BAGI GURU MGMP BAHASA JEPANG SE-MALANG RAYA - Indrowaty, Sri Aju -; Febriyanti, Rike -; Husna, Lailatul - (Faculty of Cultural Studies, Universitas Brawijaya, 2022)
The National Examination (UN), carried out so far, will be replaced in 2021 with the 2021 National Assessment. In this national assessment, three instruments are elements of the evaluation: Minimum Competency Assessment (AKM), Character Survey, and School Environment Survey. AKM itself is an assessment of essential competencies needed by all students at the elementary, junior high, and high school levels to develop their capacity and participate actively and positively in society. After the MOU with the Japanese Language MGMP in the Malang area with the Japanese Language Education Study Program, due to the Covid-19 pandemic, this collaboration can only be realised in 2021. The formulation of the problem from this Penmas is 1. How to make teaching materials (in brief) easier for students to understand the material taught in the form of worksheets? 2. How to write assignments and exercises to improve students' understanding of the themes taught in worksheets? The final result of this Penmas is the creation of AKM-based Japanese worksheets. Then these worksheets will be printed to get the ISSN/ISBN to increase the score for the promotion of available positions for teachers, while language education lecturers implement the Tri Dharma of Higher Education, namely Service.